Women's Experiences With Neuraxial Labor Analgesia in the Listening to Mothers II Survey: A Content Analysis of Open-ended Responses. Issue 3 (September 2016) - Attanasio, Laura; Kozhimannil, Katy B.; Jou, Judy; McPherson, Marianne E.; Camann, William
Abstract : ( Anesth Analg. 2015;121:974–980) Neuraxial analgesia provides effective pain relief with minimal effect on the fetus and without increased risk of cesarean delivery. Most studies that address the patient experience with neuraxial analgesia during childbirth utilize small numbers and broad questions. Using secondary analysis of a larger database, these authors identify themes of positive or negative experiences with neuraxial analgesia using data collected from the Listening to Mothers II survey. Questionnaires, which contained 3 open-ended questions, were completed online (n=1373) or using telephone interview (n=200); the final analysis included 914 women of childbearing age, of which 69% were white non-Hispanic, 12% African American non-Hispanic, and 13% Hispanic.